"I Didn't Know How We Were Going to Survive": U.S. Community Newspapers' Resilience During COVID-19. (28th May 2023) - Finneman, Teri; Mari, Will; Thomas, Ryan J.
ABSTRACT: As journalists dealt with a nonstop news cycle in the early months of the COVID-19 pandemic, many of their newspapers faced a financial crisis as advertising revenue sharply declined during economic shutdowns. Unable to rely on their centuries-old, advertising-centric business model, U.S. community newspapers had to turn to other means to survive. This study features oral histories with 24 journalists and state newspaper association directors in six states for a deeper understanding of how community newspapers handled the financial crisis on top of a public health crisis in early 2020. Through our interviews, journalists at locally-owned newspapers described a variety of strategies, ranging from public- to market-funded, that they used in order to keep publishing. For many, this meant accepting government funding through the Paycheck Protection Program despite the industry's longtime prior resistance to a public-funding model. Community newspapers also turned to donations, grants, and other creative market strategies. However, even after the disruptions of COVID-19 presented new revenue options, community journalists say a complex road still exists for changing their business model.